2019
DOI: 10.1128/aem.01237-19
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Furfural-Induced Genomic Instability Using a Yeast Model

Abstract: Furfural is an important renewable precursor for multiple commercial chemicals and fuels; a main inhibitor existing in cellulosic hydrolysate, which is used for bioethanol fermentation; and a potential carcinogen, as well. Using a genetic system in Saccharomyces cerevisiae that allows detection of crossover events, we observed that the frequency of mitotic recombination was elevated by 1.5- to 40-fold when cells were treated with 0.1 g/liter to 20 g/liter furfural. Analysis of the gene conversion tracts associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…The frequency of aneuploidy events (6.3 × 10 –2 per genome per division) was even higher than that of LOH events. By contrast, LOH events occur at a much higher rate than aneuploidy events in wild-type cells under normal conditions (O'Connell et al 2015 ; Qi et al 2019a , b ). Interestingly, we found that heat shock produced more trisomic chromosomes than monosomic chromosomes in yeast, and the opposite result was found in carbendazim-treated cells (spindle assembly inhibition leads to failure in pulling the chromatid into cells).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of aneuploidy events (6.3 × 10 –2 per genome per division) was even higher than that of LOH events. By contrast, LOH events occur at a much higher rate than aneuploidy events in wild-type cells under normal conditions (O'Connell et al 2015 ; Qi et al 2019a , b ). Interestingly, we found that heat shock produced more trisomic chromosomes than monosomic chromosomes in yeast, and the opposite result was found in carbendazim-treated cells (spindle assembly inhibition leads to failure in pulling the chromatid into cells).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies used the diploid S. cerevisiae strains produced by crossing two heterozygous haploid strains to determine genomic instability caused by DNA replication stress (Zheng et al 2016 ; Sui et al 2020 ), oxidative stress (Qi et al 2019a , b ; Zhang et al 2019 ), and small molecular compounds (Qi et al 2019a , b ; Sheng et al 2019 ). The abundant single nucleotide polymorphisms (SNPs) between the two homologs in the diploid strains allow for the identification of genetic events across the yeast genome at high resolution through SNP microarray and genome sequencing (Guo et al 2017 ; Yin et al 2017 ; Zheng and Petes 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, chromosomal rearrangement can result from mutations of genes (such as SOD1 and TSA2 ) involved in the anti-oxidative systems [ 58 , 107 ] and intracellular ROS accumulation induced by extracellular stressors. Qi et al [ 108 ] found that exposure to furfural, a major inhibitor existing in the cellulosic hydrolysate used for bioethanol fermentation, led to enhanced rates of chromosomal rearrangements in yeast cells. Although furfural cannot cleave DNA directly, the authors observed frequent in vivo DNA breaks due to accumulation of intracellular ROS [ 108 ].…”
Section: Spontaneous and Genotoxic Factor-induced Chromosomal Rearmentioning
confidence: 99%
“…Qi et al [ 108 ] found that exposure to furfural, a major inhibitor existing in the cellulosic hydrolysate used for bioethanol fermentation, led to enhanced rates of chromosomal rearrangements in yeast cells. Although furfural cannot cleave DNA directly, the authors observed frequent in vivo DNA breaks due to accumulation of intracellular ROS [ 108 ]. It is likely that prolonged exposure of yeast cells to the recombinogenic agent under industrial conditions could quickly lead to loss of selected desirable traits of industrial yeast strains.…”
Section: Spontaneous and Genotoxic Factor-induced Chromosomal Rearmentioning
confidence: 99%
“…HSF breads accounted for about 20% less furfural than standard breads. Furfural has a leading role in the aroma of bakery products [23], but it was recently investigated as a potential carcinogen [69,70]. The concentration of octadienal dimethyl (Z) naturally occurring in raw hemp seeds, significantly increased in HSF bread as effect of S. cerevisiae fermentation.…”
Section: Aldehydesmentioning
confidence: 99%